Pengaruh Pengetahuan dan Penggunaan Kosmetik Pemutih Terhadap Kulit Wajah Pada Mahasiswi STIKes Persada Husada Indonesia - Herlina Herlina; Evi Vestabilivy (Jurnal Persada Husada Indonesia, 2019)
Today many young women who use cosmetics, they are tempted to use beauty products, because they can whiten facial skin quickly. They do not know the impact that will occur from the use of cosmetics. BPOM found 43 types of cosmetics containing hazardous ingredients consisting of eye makeup, makeup, skin care, bath preparations and nail preparations. The amount of whitening cosmetics that are harmful makes the facial skin flake and thin so that the skin becomes more sensitive because the thin skin is close to nerves and blood vessels, in short-term use this substance will give a reaction of redness, irritation and burning sensation because the skin loses layers for the skin. due to peeling. This study aims to determine the effect of knowledge and use of whitening cosmetics on facial skin in PHI STIKes female students. Analytical research method with Cross Sectional approach. Population is all students who are active in the learning process. The independent variable of knowledge, the use of whitening cosmetics and the dependence of facial skin. The results obtained from this study were that there was a significant influence between the use of whitening cosmetics (p-value = 0.002) on facial skin, whereas from observations the condition of female facial skin was in a good category (78%), the results showed that only a small percentage of female students problems with facial skin health. The use of cosmetics in accordance with the skin type will have a positive impact on the skin while the use of cosmetics that do not suit the skin type will have a negative impact on the skin. The conclusions of the study are to be more careful and careful and require carefulness in choosing cosmetics in adolescence.